From Adam Smith to John Stuart Mill: The Quest for Equilibrium in Classical Economics - Yılmaz, İlkay and Aktaş, Erkan (Journal of Applied And Theoretical Social Sciences, 2025)
Introduction: This study examines how the concept of equilibrium evolved in Classical Economics, focusing on prominent thinkers from Adam Smith to John Stuart Mill. The research is important because it sheds light on how foundational economic ideas regarding competition, production, and distribution inform present-day theories and policies. Method: This study was carried out based on a literature review and theoretical analysis; in addition to the works of the Classical Economists themselves, academic studies and commentaries related to their work and ideas were also utilized. Results or Findings: The analysis shows that the confidence Smith and Say placed in market mechanisms is significantly constrained by the potential instabilities and the stationary state thesis highlighted by Malthus and Ricardo. Mill’s approach indicates that the economy’s long-term equilibrium is shaped by both income distribution and social norms, while in the short term, actions taken by market participants based on incorrect forecasts or incomplete information can result in disequilibrium. Discussion or Conclusion: The results imply that Classical Economics presents a rich, nuanced view of equilibrium—one that balances the self-correcting nature of markets with critiques about demand, distribution, and long-run stagnation. These insights remain relevant for contemporary discussions on growth, sustainability, and policy interventions. Future research could compare the classical equilibrium framework with modern theoretical models to explore how historical perspectives continue to shape economic thought and policymaking.